Energy planning and sustainable development of Pakistan. Issue 1 (18th October 2018) - Hayat, Farah; Khan, Abid Ali; Ashraf, Muhammad Arif
Abstract : Purpose: Analysis of relationship between energy and growth offers the sustainable energy pathway for a country's sustainable economic development. This study aims to focus on the evaluation of the Pakistan's energy system using long-run energy alternative planning (LEAP) modeling framework through different growth scenarios. Design/methodology/approach: Principal component analysis has been adopted for indicators index formation. Study period of 1980 to 2030 is covered by forward and backward simulations in LEAP software. Findings: The study reveals that current energy policy does not have the potential to lead the country toward a desired goal of economic sustainability. Research limitations/implications: In falling off scenario, negative growth rate (-5 per cent) assumption is also debatable; LEAP shows an error in the analysis and takes the last positive available value for any further analysis as a default. This case could have been simply omitted from results but for research contribution, the computations for this case are also reported. Practical implications: Long-range energy alternative planning model has been applied to answer the corresponding question for simulation period of 1980 to 2030 to better compare the past trend and future expectations. Critical analysis of four selected scenarios (BAU, moderate, advanced and falling off) indicate that energy policy of Pakistan is poorly managed to maintain energy system's effectiveness. Social implications: As far as statistical difference is concerned, early years have more fluctuation; however, from 2009, curve flattens for energy consumption and energy demand. The increasing demand of energy impacts the society and hence disturbs all sectors. Originality/value: Policymakers have been so dragged off from the main route to sustainability, despite all odds there is a huge unexplored potential in the country for use to move in step with the world for a better tomorrow. The study educates the policymakers to comprehend the future energy scenarios and make rational decisions based on the study outcomes.